ADAPTATION OF LINEAR-QUADRATIC MODEL FOR PLANNING NEUTRON THERAPY REGIMENS - V. A. Lisin; V. V. Velikaya; I. A. Miloichikova (Сибирский онкологический журнал, 2016)
Based on the fact that the parameters of the linear-quadratic model for neutron therapy were found, the comparison of single therapeutic doses in neutron therapy, calculated using the TDF (time-dose-fractionation) and linear-quadratic (LQ) models were carried out. The calculation results were shown to be in good agreement. We also compared the degree of discrepancy in results calculated using the TDF and LQ models between neutron therapy and gamma therapy. It was shown that the use of the linear-quadratic model designed for neutron therapy is capable of providing adequate control for radiation-induced tissue reactions.